Natural Products in Cardiovascular Diseases: The Potential of Plants from the Allioideae Subfamily (Ex-Alliaceae Family) and Their Sulphur-Containing Compounds - Jorge M. Alves-Silva; Mónica Zuzarte; Henrique Girão; Lígia Salgueiro (Plants, 2022)
Cardiovascular diseases (CVDs) are the leading cause of mortality worldwide and, together with associated risk factors such as diabetes, hypertension, and dyslipidaemia, greatly impact patients’ quality of life and health care systems. This burden can be alleviated by fomenting lifestyle modifications and/or resorting to pharmacological approaches. However, due to several side effects, current therapies show low patient compliance, thus compromising their efficacy and enforcing the need to develop more amenable preventive/therapeutic strategies. In this scenario, medicinal and aromatic plants are a potential source of new effective agents. Specifically, plants from the Allioideae subfamily (formerly Alliaceae family), particularly those from the genus Allium and Tulbaghia, have been extensively used in traditional medicine for the management of several CVDs and associated risk factors, mainly due to the presence of sulphur-containing compounds. Bearing in mind this potential, the present review aims to gather information on traditional uses ascribed to these genera and provide an updated compilation of in vitro and in vivo studies validating these claims as well as clinical trials carried out in the context of CVDs. Furthermore, the effect of isolated sulphur-containing compounds is presented, and whenever possible, the relation between composition and activity and the mechanisms underlying the beneficial effects are pointed out.